A Cross-Sectional Study of the Prevalence of Keratoconus in Patients with Astigmatism More than Two Diopters - Sama, Zinatus; Afroz, Tamanna; Hamid, Salman Ahmed T.; Abdulmajeed, Saeema M.; Chowdhury, Imtiaj Hossain; Hasan, Md Mahmudul (Vision Science and Eye Health Journal, 2025)
Introduction: Patients with astigmatism, especially those with more than two diopters, appear to have keratoconus as a co-morbidity. Understanding the coexistence of these two diseases may aid in these patients' early detection and management. Purpose: The purpose of the present study was to establish the rate of keratoconus among the patients with >2D astigmatism in Bangladesh. Methods: 80 astigmatic patients >2D among the age group 10-45 years old participated in this cross-sectional study between May and August 2024 at Noor Makka and Makka Eye Hospitals, Dhaka, Bangladesh. Keratoconus and subclinical cases were identified by using corneal topography, slit lamp, and corneal asymmetry, along with general visual evaluation by an ophthalmology consultant. Statistical package for the social sciences (SPSS) software was used as the data analysis tool. Results: This study analyzed the socio-demographic information and the eye characteristics of people with astigmatism. Out of 80 studied participants, keratoconus appeared in 65%, mainly from the age group 17-30 (56.25%). Among the study participants, males and females were 47.50% and 52.50%, respectively. The average astigmatism level was recorded at 4.697 diopters. The research established a significant statistical correlation between Keratoconus diagnosis and corneal biomicroscopy (p = .001) and corneal topography (p = .000), where most of the keratoconus patients showed thinning patterns in their stromal structure. The research also established a connection between age and gender to keratoconus. Conclusions: This cross-sectional study revealed a high prevalence of diagnosed keratoconus among astigmatic patients, particularly affecting younger individuals.